Determinan Faktor Perputaran Karyawan Menggunakan Structural Equation Modeling (SEM) - Yuniarto, Yustinus; Fadilah, Titin Fani (Universitas Bunda Mulia, 2019)
Business competition in this case shows the public demand and supply in this case applies. The development of the business world is able to provide offers that tend to be more attractive to both experienced and non-experienced Human Resource. This makes employees in a company in a certain period tend to have consideration to move and choose more attractive offers from other companies. This study generally aims to analyze the determinants of employee turnover factors. This research is a quantitative study using Structural Equation Modeling (SEM) with a total sample of 50 people with analysis tools, namely SMART PLS 3.0. The results of this study explain in a direct effect that employee motivation is not affected by service efforts to the client as part of the work carried out by employees and also not affected by employee teamwork. However, employee motivation is influenced by relationships between employees, employee responsibilities at work, employee work behavior. The desire of employees to change jobs is influenced by employee motivation. Indirectly, the desire of employees to change jobs is not influenced by service to the client and teamwork. Conversely, the desire of employees to change jobs is influenced by factors of work relations between employees, employee responsibilities with employee motivation as mediating factors, and employee work behavior factors. Suggestions for researchers can then use export import companies originating from outside Indonesia where blending the culture of the organization will have an important role.